“Revistas e história disciplinar no Brasil: uma síntese da organização do campo em três periódicos – Revista de História, Estudos Históricos e Revista Brasileira de História (1960‐2000)" - Nascimento, Bruno César (2021)
This research aims to examine whether the formation of the community of professional historians from the 1960s to the mid-2000s in Brazil was not constituted through a set of normalization strategies in the field of disciplinary History and its practices leaked through of academic journals that would have established a set of guidelines for practitioners of the profession whose advances occur through the overcoming or exhaustion of research agendas and disputes with previous generations. It takes as a privileged locus, the appreciation of practice and textual production aimed at journals, which end up conferring a hierarchical cartography of research networks that are consolidated around certain figures, journals and academic training centers. The study sought to identify these figures, using concepts such as the scientific field, habitus, disciplinary history and power, extracted, in particular, from authors such as Foucault and Pierre Bourdieu. Characters who occupied positions in three of the most important history magazines in Brazil – Revista de História from USP, Revista Brasileira de História from Anpuh and Revista Estudos Históricos from Fundação Getúlio Vargas: editors and members of the editorial and advisory boards. This expedient made it possible to validate the raised hypothesis, verifying how this knowledge was consolidated and disseminated in a specific scenario, capturing some of its most recent changes and dynamics. By emphasizing the existence of strategic positions of pre-eminence and direction in the networks composed around those journals, as well as the generations found, this work sought to contribute to the understanding of the debates and processes of dispute experienced by the field in recent decades.